Fabrication of flexible chitosan-based polymer electrodes embedded with molybdenum disulphide nanoparticles for supercapacitor applications - Bipin S. Chikkatti; Ashok M. Sajjan; Nagaraj R. Banapurmath; S.K. Rajappa (Next Materials, 2025)
The target of this research is to inspect the electrochemical characteristics of molybdenum disulphide nanoparticles on chitosan membranes for supercapacitor applications. The interaction between molybdenum disulphide and chitosan, affinity towards water, mechanical properties and surface morphology are checked by Fourier transform infrared spectroscopy, water contact angle, universal testing machine and scanning electron microscopy, respectively. Among the established membranes 1.5 wt% of molybdenum disulphide on chitosan displays significant electrochemical presentations. It exhibited a maximum specific capacitance of 345.8 F g−1 at a current density of 0.2 A g−1, maximum energy density of 22.2 Wh kg−1 and maximum power density of 544 W kg−1. A cycle study discloses 96 % capacitance retention after 5000 cycles. Flexible molybdenum disulphide membranes are likely to be a powerful combination for supercapacitors.